Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Problem Solving Untuk Meningkatkan Disiplin Belajar Pada Peserta Didik - Barkah Shabrina; Asni Asni (Journal on Education, 2024)
This research is entitled "The Effect of Group Tutoring Using Problem Solving Techniques to Improve Learning Discipline in Class VIII Students of YWPM Jakarta Middle School". Learning discipline influences student success. However, many people are undisciplined, such as coming late, disturbing friends while studying, not wearing shoes, and leaving lessons without permission. This research aims to improve learning discipline through group guidance with problem solving techniques for YWPM Jakarta Middle School students. The method used is quantitative with a one group pretest-posttest model. The research population was 33 people and the sample was 10 people, taken by purposive sampling. The research instrument was a questionnaire, with validity test results of 42 valid items out of 55 items. The reliability of the calculation shows a value of 0.924. The normality test shows that the data is normally distributed with a significant value > 0.05. Hypothesis testing using the Paired-Samples Test shows Sig (2-Tailed) 0.000 < 0.05, so Ha is accepted. The results and conclusions of the research show that group guidance using problem solving techniques has the effect of improving the learning discipline of class VIII students at YWPM Jakarta Middle School.